Essential structure of orexin 1 receptor antagonist YNT-707, Part II: Drastic effect of the 14-hydroxy group on the orexin 1 receptor antagonistic activity. Issue 4 (15th February 2018) - Ohrui, Sayaka; Yamamoto, Naoshi; Saitoh, Tsuyoshi; Kutsumura, Noriki; Nagumo, Yasuyuki; Irukayama-Tomobe, Yoko; Ogawa, Yasuhiro; Ishikawa, Yukiko; Watanabe, Yurie; Hayakawa, Daichi; Gouda, Hiroaki; Yanagisawa, Masashi; et al.
Graphical abstract: Abstract: The 14-dehydration- and 14-H derivatives of the orexin 1 receptor (OX1 R) antagonist YNT-707 (2 ) were synthesized. The obtained derivatives showed higher affinities for OX1 R than the corresponding 14-hydroxy derivatives. The conformational analysis suggested that the 17-sulfonamide groups in the derivatives without the 14-hydroxy group have a greater tendency to be oriented toward the upper side of the D-ring compared with the 14-hydroxy derivatives. Additionally, the 14-dehydration-derivative with 6α-amide side chain showed significantly higher affinity than the 14-hydroxy derivative, while the corresponding 14-H derivative showed only slightly higher affinity. Thus, the 14-hydroxy group strongly affects the affinity of the antagonist for the OX1 R.